“Happy” Goats - Marco Reggio; Suleiman McShane; Erin Clancy (Humanimalia, 2025)
This text was originally published in Italian as the first chapter (Dérive #1) of Marco Reggio’s book Cospirazione Animale. Tra azione diretta e intersezionalità [Animal Conspiracy: Between Direct Action and Intersectionality]. Additional footnotes have been provided by the author for this English translation, with some information on the Italian context. The chapter deals with issues of species, gender, and coloniality that emerged in the praxis of the Italian anti-speciesist movement over the past fifteen years. In particular, Reggio gives an account of his experience as an activist and researcher facing the death of an Ethiopian woman, Agitu Ideo Gudeta, who fled her country under political persecution to open a goat farm in Italy, where she was assaulted and killed by a co-worker. Reggio interrogates the conflict between the privilege that entails being able to criticize and take distance from animal farming (which was hardly achievable from Gudeta’s standpoint), and the impossibility of endorsing and celebrating the “happy meat” paradox from an animal liberation perspective (like all farmers, Gudeta sent baby goats to the slaughter in order to be able to milk their mothers). Reggio articulates his reflection along the lines of Frantz Fanon’s notion of the “zone of non-being” and Judith Butler’s aporetic “embarassment” in the face of the inexhaustible plurality of identities that cloak the subject (potentially opening the doors to the more-than-human).